Book Review: Interpreting the Environment at Museums and Historic Sites by Reid and Vali - V. M. Robertss (EXARC Journal)
Interpreting the Environment at Museums and Historic Sites is a textbook and a call to action. In the midst of the Anthropocene, Debra A. Reid and David D. Vail argue, museums and conservation areas should attend to their environmental assets, tell environmental stories, and take an activist role in encouraging better stewardship.